In-band and in-service measurement of satellite antenna parameters during sun outages - Conanan, Virgilio D. (Animo Repository, 2003)
Testing satellite antenna systems for compliance with various standards can be time-consuming and expensive because they call for a controlled environment using shielded RF anechoic chamber, certified antenna test ranges or by measuring the satellite transponder power while physically moving the antenna bore sight elevation and azimuth. This thesis presents a method of measuring satellite receiving antenna parameters without moving the antenna, by using the sun as a signal source. Twice a year, during the spring and fall equinoxes, the sun passes in conjunction with the satellite. During these times, the sun emits noise and renders the earth station unusable hence the event is called the sun outage. The increase in noise output at the earth station receiver, when plotted correspondingly with time, indicates the receiving antenna pattern. The monitoring system consists of a PC-based measuring system that is interfaced with either a band-limited power meter, a spectrum analyzer or a satellite receiver having a calibrated DC AGC output. The sun essentially scans the satellite antenna bore sight on the peak of the sun outage period. This method creates time-stamped noise level measurements, which converts time to degrees and when plotted on a chart would reveal the actual operating characteristics of the antenna under test such as gain, beam width and side lobe characteristics. These instruments are made during the sun outage periods in the spring and fall equinoxes, but out-of-service tests can be performed at other times.